Business management business 2000 - Burrow, James L. (South-Western Thomson Learning, 2002)
Business 2000: Business Management is the best way to introduce management skills. Information on the business environment and ownership, management functions and leadership, communication and information systems, production and marketing management, and more, is incorporated to fulfill the user's needs!